Which is better between gold and its share? A context for designing a financial mathematical task - Ramadhan, M. Hasbi; Zulkardi; Putri, Ratu Ilma Indra; Resti, Yulia (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Financial mathematics is a crucial discipline for students, mainly when taught using real-life contexts such as gold and its share. It can help students develop practical solutions to financial problems. This study aimed to design a financial mathematics task for Vocational High Schools (VHS) that is valid, practical, and demonstrates potential effects utilizing the Pendidikan Matematika Realistik Indonesia (PMRI) approach in the context of gold and its share. The research employed a design research methodology, specifically a development study involving two primary phases: preliminary and formative evaluation. The latter included multiple stages of prototype development, beginning with self-evaluation, then expert review, one-on-one sessions, small group trials, and culminating in a field test. The study was conducted with 44 eleventh-grade accounting students at VHS 1 Jambi City, consisting of 3 students for the one-to-one phase, 6 for the small group phase, and 35 for the field test phase. Data were collected through tests, interviews, documentation, and observations. The findings indicate that the financial mathematics task designed using the PMRI approach, contextualized in gold and its share, was valid, practical, and positively impacted student learning. Students not only developed a deeper understanding of real-world financial issues but also enhanced their decision-making abilities in financial contexts. Additionally, teachers expressed a greater willingness to adopt the PMRI approach in their instruction, suggesting that this context can effectively support the teaching of financial mathematics in vocational high schools.